2015
DOI: 10.5746/leia/asean_integ_elt
|View full text |Cite
|
Sign up to set email alerts
|

ASEAN Integration and the Role of English Language Teaching

Abstract: Malaysia has invested heavily to develop education and language competencies for national and transnational needs, including English for international communication. Any attempt to meet English language needs of ASEAN partners could benefit from lessons from the past and a focus on productive multilingualism, especially in a linguistically diverse nation There is a history of addressing the urban and rural divide with various projects to build English language skills for a knowledge-based economy, yet there ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, every government starts their human capital development from the curriculum of its nation. As said by Stroupe and Kimura (2015) "in the last few decades, economic growth, political change, and educational challenges have rapidly changed the Asian region dynamically. Educational challenges include the growth of education and the curriculum used in a country that has a significant impact" (p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, every government starts their human capital development from the curriculum of its nation. As said by Stroupe and Kimura (2015) "in the last few decades, economic growth, political change, and educational challenges have rapidly changed the Asian region dynamically. Educational challenges include the growth of education and the curriculum used in a country that has a significant impact" (p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The university supports through the grants are provided by students and lecturers for a short visit to universities in foreign countries. Stroupe and Kimura (2015) reported that the challenges of ASEAN Economic community are in the use of English as an international language. It needs improvement in the English language proficiency of the teachers, students, and government officials.…”
Section: A Institutional Motivation In Emimentioning
confidence: 99%